Mechanisms of specific immunological unresponsiveness to bacterial lipopolysaccharides. - Elkins, K L (1987)
Low-dose priming of mice with Escherichia coli O113 lipopolysaccharide (LPS) results in the development of immunological memory, whereas low-dose priming with E. coli O55 LPS or Serratia marcescens LPS induces significant antigen-specific unresponsiveness. All three preparations of LPS induced proliferation of mouse splenocytes with similar time course and [3H]thymidine uptake. There was no correlation between the small amounts of serum antibody detected by enzyme-linked immunosorbent assay after low-dose priming and the subsequent generation of either memory or unresponsiveness. Further, the passive transfer of small amounts of LPS-specific antibody had no significant effect on the magnitude of the plaque-forming cell (PFC) response elicited after subsequent immunization. Reduction of the PFC response to E. coli O55 LPS occurred after low-dose priming of nu/nu (as well as nu/+) mice; however, unresponsiveness could not be generated in nu/nu mice by low-dose priming with S. marcescens LPS. Thus, although the development of low-dose unresponsiveness to S. marcescens LPS appears to involve T cells, the response of E. coli O55 LPS does not. Enhancement of the primary PFC response to S. marcescens LPS could be transferred with low-dose primed spleen cells depleted of Lyt-2+ T cells; this suggests that the magnitude of the PFC response to this preparation of LPS is negatively influenced by Lyt-2+ T cells and positively influenced by Lyt-2- spleen cells (i.e., L3T4+ T cells). These findings indicate that T cells appear to be involved in regulating the magnitude of the antibody response to some types of bacterial LPS.